Perbandingan Hasil Tanangkapan Udang Rebon (Acetes Sp) Alat Tangkap Togok Pada Waktu Pasang Dan Surut Di Perairan Kuala Tungkal Kabupaten Tanjung Jabung Barat - Alhumaid, Faiqul Hafidz; Mairizal, Mairizal; fauzan, Fauzan Ramadan (Mantis Journal of Fisheries, 2026)
The potential of Kuala Tungkal waters includes various fish and shrimp such as grouper, anchovies, rebon shrimp, crabs, and cuttlefish. Togok, a passive fishing gear, is commonly used to trap organisms with the help of currents. This study aimed to compare catches at high and low tide and identify main and by-catch using experimental fishing with 5 togok units over 15 days. Results showed rebon shrimp dominated the catch (57% at high tide; 50.23% at low tide) as the main catch, while others were bycatch. Differences were influenced by shrimp behavior, net position, and gear selectivity. In conclusion, togok is more effective at low tide, with rebon shrimp as the primary catch.